Robot Pengikut Posisi dengan Menggunakan Filter Warna HSV - Fitrah Triatmojo; Budi Sugandi (JURNAL INTEGRASI, 2018)
Advancement in digital processing technology have benefited to the human. One of the benefits of image processing is to improve the quality of an image, eliminate noise in and identify objects. By utilizing the technology, it can be developed a system that can detect and track objects. In this article, we develop a system to detect and track an object. We use the HSVcolor filter, erosion, dilation, and thresholding methods to detect the object. To measure the distance between object and robot, we apply the mathematical regression formula. The output of the equation is then used as actuator for the dc motor. The results achieved in this study is system can detect object in the distance range 50-180 cm and follow the object in the range 60-150 cm.